INFORMATION AND COMMUNICATION TECHNOLOGY: MENDORONG EFISIENSI KINERJA AUDITOR SELAMA PANDEMI COVID-19 - Nabila, Khansaa; Sasmita, Maulidya Eka; Adawiyah, Robbiatul; Putri, Dhika Maha (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The evolution of information technology is going rapidly, supported by the COVID-19 pandemic where all activities related to face-to-face and gathering activities are limited. Many companies already have implemented ‘work from home’ policies for their employees, including auditors. Responding to this phenomenon, many companies have finally changed the auditor’s work system by applying remote audit techniques based on the use of ICT tools.The application of Information and Communication Technology (ICT) will minimize direct contact, and also reduce audit. The purpose of this study is to examine the effectiveness and efficiency of auditor's performance by applying remote audit techniques using ICT. In this study uses a qualitative approach. By to obtain a depth understanding of the object of research related to the existing problems such as the risks and to find out whether the application of ICT in remote audit techniques is effective and efficient when it’s carried out during a pandemic. A literature study is employed to assess the efficiency of ICT performance in remote audit techniques. The results of this study indicate that the application of ICT in supporting the remote audit process during the Covid-19 pandemic is the best way. However, we should still paying attention to the appropriateness of the devices, the signal, and data security protection so that the evidences provided by the auditee to the auditors are remains usable and reliable.